Pedagogia da educação infantil, gestão escolar e liderança pedagógica: um estudo de caso multicontexto numa pedagogia transmissiva e numa pedagogia participativa - Pereira, Jorgiana Ricardo (2019)
This research aimed to deepen theoretical and practical knowledge about the Pedagogy of Childhood, in contexts of Early Childhood Education. We sought to identify how the Pedagogy developed in the daily life of early childhood education institutions contemplate the specificit ies of this stage of education. In these contexts, we sought to observe if and how the managers act in the pedagogical l eadership, and how they develop and concretize the Pedagogy of Early Childhood Education. The theoretical bases are in the field of Pedagogy specifically the Pedagogy of Early Childhood Education that has been developed in Brazil, the Pedagogy of Relatio n and Listening developed in Reggio Emilia (Italy), and the Pedagogy in Participation, the pedagogical perspective of the Child Association of Portugal . T he empirical research was a multicontext case study, carried out in two Early Childhood Education Inst itutions. Data collection methods were participant observation, document consultation, questionnaire and semi structured interview. Participated in the research: managers, teachers, assistants of early childhood education, other professionals and family of children. In the first case study, we analyzed the Pedagogy that guided the work of managers and how it was carried out in the daily life of the institution. As a result, we observed that such Pedagogy reflected a pedagogical ideal guided by assistentiali sm, with a transmissive education perspective, and determined by the bureaucratic political power. In this context, the specificity of early childhood education was extremely precarious. The principal and the two pedagogical coordinators (PCs) were limited to the control, the management of norms, the maintenance of formalities and the pedagogy practiced in the institution. In this context, the principal's leadership was authoritarian, oriented to exercise control and keep teachers and PCs subordinate to her decisions. The performance of the PCs revealed many impotencies in the field of pedagogical leadership, standing in the bureaucratic pedagogical management. Thus, the performance of the managers made the institution work, but did not support the change an d transformation of educational practices towards the development and implementation of the Pedagogy of Early Childhood Education. The results of the second case study, conducted in an institution where a participatory early childhood education was practic ed, show the relevance of the experiential learning of a specific pedagogy to organize and realize the pedagogical dimensions in daily life, in coherence with the specificity of early childhood education. In this context there was the pedagogical leadershi p of the principal and also the teachers. The leadership performed by the principal as well as the leadership by the teachers constituted a mutual relationship; both supported each other to realize the purpose of developing and sustaining a participatory p developing and sustaining a participatory pedagogical praxis in daily life, based on the edagogical praxis in daily life, based on the Pedagogy of Early Childhood Education that guided the educational work in the institution.Pedagogy of Early Childhood Education that guided the educational work in the institution. Among the conclusions drawn at the end of the research process, we emphasize that the Among the conclusions drawn at the end of the research process, we emphasize that the genuine change of Pedagogy dependgenuine change of Pedagogy depends on a collective work and willingness to change, which s on a collective work and willingness to change, which is not only spontaneous, but also provoked.is not only spontaneous, but also provoked. Change depends on building knowledge that Change depends on building knowledge that stimulates the change. In this process, it is necessary that the continuing education of early stimulates the change. In this process, it is necessary that the continuing education of early childhood professiochildhood professionals (managers, teachers and assistants) be guided by and for the nals (managers, teachers and assistants) be guided by and for the professional daily life, the rprofessional daily life, the real and noneal and non--abstract daily life.abstract daily life. TThat is centered on professionals hat is centered on professionals and children, and guided by a specific Pedagogy, that is, by the pedagogical dimensions of and children, and guided by a specific Pedagogy, that is, by the pedagogical dimensions of ththis Pedagogy (educational spaces and time, pedagogical documentation, planning, evaluation is Pedagogy (educational spaces and time, pedagogical documentation, planning, evaluation and interactions) and by a collaborative pedagogical culture. This Pedagogy is effective in and interactions) and by a collaborative pedagogical culture. This Pedagogy is effective in daily life through the action of the entire educational team, in each and daily life through the action of the entire educational team, in each and all of those all of those dimensions.dimensions.